Mycological quality of masmin and mycotoxigenicity - Mubashira,p v (KUFOS, 2015)
Abstract- Masmin is a traditional culinary product of Lakshadweep Islands that is prepared by cooking in sea water followed by alternate drying and smoking till the moisture content is reduced below 10%. Growth of certain types of fungi is known to enhance the acceptability of the product due to the typical flavor imparted but growth of toxigenic fungi during moulding can lead to food poisoning.